Franco Cordero: il polemista - Boggione, Valter (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
Cordero’s entire production is animated by a strong polemical charge, aimed at the Church and Berlusconi, emblematic expressions of an Italian spirit dominated by a lack of ethical seriousness, selfishness, familyism. The controversy, which owes much to Leopardi’s Operette morali, arises from the rejection of all dogmatism, of the cult of the self, of the subjugation of consciences to party or personal interest, and is animated by an almost prophetic desire to announce enlightenment. However, the Catholic education is evident not only in moralism and in a biblical imagery, but also in the fierce investigation into the origin of evil. Cordero’s writing is full of fantastic inventiveness, as evidenced by the dozens of nicknames applied to Berlusconi, starting with the Caiman, and combines in a singular way an Enlightenment desire for conceptual clarity and concentration with the baroque taste of the list, of grotesque deformation and surreal and the use of figures of exasperation.